The new phylogenesis of the genus Mycobacterium. (March 2015) - Tortoli, Enrico; Fedrizzi, Tarcisio; Pecorari, Monica; Giacobazzi, Elisabetta; De Sanctis, Veronica; Bertorelli, Roberto; Grottola, Antonella; Fabio, Anna; Ferretti, Pamela; Di Leva, Francesca; Serpini, Giulia Fregni; Tagliazucchi, Sara; et al.
Abstract: Phylogenetic knowledge of the genus Mycobacterium is based on comparative analysis of their genetic sequences. The 16S rRNA has remained for many years the only target of such analyses, but in the last few years, other housekeeping genes have been investigated and the phylogeny based on their concatenated sequences become a standard. It is now clear that the robustness of the phylogenetic analysis is strictly related to the size of the genomic target used. Whole genome sequencing (WGS) is nowadays becoming widely accessible and comparatively cheap. It was decided, therefore, to use this approach to reconstruct the ultimate phylogeny of the genus Mycobacterium . Over 50 types of strains of the same number of species of Mycobacterium were sequenced using the Illumina HiSeq platform. The majority of the strains of which the whole sequence was already available in GenBank were excluded from this panel with the aim of maximizing the number of the species with genome available. Following assembling and annotation with proper software, the phylogenetic analysis was conducted with PhyloPhlAn and the pan-genome analysis pipeline. The phylogenetic three which emerged was characterized by a clear-cut distinction of slowly and rapidly growing species with the latter being more ancestral. The species of the Mycobacterium terrae complex occupied an intermediate position between rapid and slow growers. Most of the species revealed clearly related and occupied specific phylogenetic branches. Thanks to the WGS technology, the genus Mycobacterium is finally approaching its definitive location.